Дом: роман / Федор Абрамов - Абрамов Федор Александрович (Библиотека российского романа, 1984)
Экземпляры: СБ (20210113) / Инвентарный номер: 11861 / Цена: 1.20 / Сис.шифр: Р2 / Авт.знак: А 16 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6